Genes expressing carbapenemase resistance present in Pseudomona aeruginosa - Oliva Menacho, José Enrique (2021)
Objective. To describe the genes expressing carbapenemase resistance present in Pseudomona aeruginosa. Methods. The scientific literature was reviewed using the PRISMA method during February 2020 in the Pubmed, Scopus and Scielo databases. Results. The polymerase chain reaction (PCR) is described as the most commonly used technique; in addition, molecular white hyperexpression genes of multiple ejection pumps that generate bacterial resistance were found. Conclusions. Conventional and multiplex PCR is the most widely used technique for the diagnosis of genes that express resistance to carbapenemases present in Pseudomona aeruginosa of patients with cystic fibrosis, being the most standardized and have high sensitivity, and specificity, also having detected IMP, VIM, OXA, MexAB-OprM, MexCD- OprJ, MexEF-OprN and MexXY-OprM genes.